Oral Metformin Treatment Counteracts Adipoinsular Axis Dysfunction in Hypothalamic Obese Rats. (5th April 2015) - Castrogiovanni, Daniel; Ongaro, Luisina; Zuburía, Guillermina; Giovambattista, Andrés; Spinedi, Eduardo
Abstract : Rats neonatally treated with monosodium L-glutamate (MSG) are deeply dysfunctional in adulthood. We explored the effect of an oral low dose of metformin treatment in male MSG rats on adipoinsular axis and visceral adipose tissue (VAT) dysfunctions, in both basal (nonfasting) and endotoxemia conditions. MSG rats, treated or not treated with metformin (30 days prior to experimentation), and control litter-mates (CTR) were studied at 90 days of age. Peripheral concentrations of glucose, lipids, and hormones were determined in basal and post-lipopolysaccharide (LPS) treatment conditions. Food intake and body weight (BW) were recorded and VAT mass and leptin mRNA levels were evaluated. Data indicated that MSG rats were lighter and displayed hypercorticosteronemia, hypophagia, adipoinsular axis hyperactivity, and enhanced VAT mass associated with an increased leptin gene expression. Interestingly, metformin-treated MSG rats corrected BW catch-up and counteracted VAT (mass and leptin mRNA level) and adipoinsular axis (basal and post-LPS) dysfunctions. Thus metformin treatment in MSG rats is able to correct several VAT and metabolic-endocrine dysfunctions. Our study suggests that a low-dose metformintherapy is effective to correct, at least in part, adipoinsular axis dysfunction in hypertrophic obese phenotypes, such as that of the human Cushing syndrome.